School-to-school collaboration to deliver effective CPD. (28th February 2019) - Cunningham, Maria
Abstract : The benefits of school-to-school collaboration for effective CPD delivery can be far-reaching.Maria Cunningham looks at some practical steps schools might take to overcome the barriers and make inter-school CPD collaborations work